The plant microbiome: the dark and dirty secrets of plant growth - Tkacz, A; Poole, P (Wiley, 2020)
This article is about life underground. More specifically it is about the rhizosphere, the zone where plant roots meet the soil. The whole of terrestrial life depends on a few inches of soil. Soil is complicated. The nature of the soil is shaped by the presence of roots. In turn, the microbes in the soil immediately surrounding roots have a profound influence on plant growth and development. The soil microbiome is the community of soil microorganisms. Sampling and analyzing the soil microbiome and the way in which microbes and roots recognize and associate with each other are technically challenging. Here, we discuss new ways to reveal what is happening hidden beneath the soil surface.